(untitled) (Naturalistic: Jurnal Kajian dan Penelitian Pendidikan dan Pembelajaran, 2025)
This research aims to develop a differentiated interactive digital module assisted by grid paper for teaching plane geometry area concepts in elementary schools. The study adopts the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) to systematically guide the module development process. The interactive digital module integrates grid paper as a concrete visual aid to help students visualize and calculate the area of plane geometric shapes, accommodating different learning abilities through differentiated activities. Data collection techniques include expert validation, student and teacher response questionnaires, and pre-test and post-test assessments to measure learning outcomes. The results indicate that the developed module meets the criteria for validity, practicality, and effectiveness. The interactive features and scaffolded learning activities enhanced students’ understanding of plane geometry concepts and increased their engagement in mathematics learning. This study contributes to the advancement of innovative and inclusive teaching practices in mathematics, providing a model that supports differentiated learning needs.